On the use of optoelectronic motion registration systems in biomechanical analysis of strike techniques - Vitaliy Kashuba; Yurii Litvinenko; Ilia Vako (Kazimierz Wielki University, 2017)
Topicality. Sports and technical skills, as an element of a holistic process of sports training, occupy one of the priority places in the overall structure of sports skills. The study, formation, improvement and development of the most rational models of sport technique are closely related to the use of modern video recording systems. The task of the study is to analyse the knee strike technique, applied by the athletes of different qualifications with the help of "Qualisys" optoelectronic system. Results of the research. Analysis of highly skilled athletes' competitive activities shows that a knee strike is mainly used in close combat. Much less often such a strike can be put in a jump from a long or average distance. In our work, we have analysed the technique of right knee strike, performed from the starting position characteristic of close combat. Conclusions. When studying the biokinematic structure of the knee strike technique, used by athletes of different qualification, differences in the dynamics of changes in the speed of the lower extremity joints on athlete' impact side of were found, which indicates higher coordination of movements, performed by highly skilled athletes. Thus, regarding highly qualified athletes the peaks of the maximum speed of their ankle and knee joints coincide in time, contrary to the skilled athletes. The speed of the skilled athletes' ankle and hip joints at certain times is higher than those of highly skilled. However, the maximum value of speed of the highly skilled athletes' strike link, as a rule, is higher on average by0.5 m ∙ s-1. The general patterns include the reduction of the resulting knee speed for athletes of different qualification at the time of strike performance in reference to the maximum values that precede the strike interaction.